THE RELATIONSHIP OF WOMEN WORKERS WITH DEVELOPMENT FROM THE PERSPECTIVE OF GAINING THEIR ECONOMIC FREEDOM AND SECURING THE FUTURE OF THEIR CHILDREN - Bediha Şahin (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This research focuses on the impact that women's participation in the workforce has on development. In this context, 12 women and 4 employer representatives were interviewed in an industrial factory located in Ankara’s Sincan region. Data were collected during the interview with the use of a semi-structured questionnaire. The duration of the interviews with the participants was approximately 90 minutes. After deciphering the interviews, women's narratives and the concepts of modernization and conflict theories were used to form thematic analysis units. In this context the themes of obstacles to women's employment, reflection of rural poverty to the city (rural poverty-urban poverty), the effect that women's work in the workplace has on development (Female workers' gains in terms of economic freedom - Their children's becoming a qualified workforce by getting education) and identification of female workers with their work - sense of belonging were determined. According to the results of the research, it has been detected that the participating women workers entered business life due to compulsory reasons, gained their economic freedom and stood on their own feet, it was effective that they worked to secure the future of their children and earned money, that they loved their job very much and were satisfied with their work. It was concluded that women do not have an awareness of development, but their working situation contributes to the development of both them and the country.